2017
DOI: 10.1017/s1041610217002241
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the built environment for people with dementia in East and Southeast Asian nursing homes: a scoping review

Abstract: The review found that the eight principles of design, when applied with cultural sensitivity in countries in East and Southeast Asia can identify gaps in knowledge of the design for dementia enabling environments and suggest areas for improvement. An assessment tool based on the principles of design will be able to provide a guide for stakeholders in the design, development, or modification of nursing home environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 34 publications
(76 reference statements)
1
21
0
Order By: Relevance
“…In Singapore, older adults aged 65 years and above make up 14.4 percent of the population, with the prevalence of dementia being 10 percent of older adults (Subramaniam et al, 2015;Sun & Fleming, 2018;Government of Singapore, 2019). With the growing ageing population, population of people living with dementia, and an old age support ratio of four and a half working adults to one older adults above 65, there is a growing number of residential aged care facilities developed to accommodate those who cannot, or choose not to, live in the community (Government of Singapore, 2019; Ministry of Health Singapore, 2019).…”
Section: Significancementioning
confidence: 99%
See 3 more Smart Citations
“…In Singapore, older adults aged 65 years and above make up 14.4 percent of the population, with the prevalence of dementia being 10 percent of older adults (Subramaniam et al, 2015;Sun & Fleming, 2018;Government of Singapore, 2019). With the growing ageing population, population of people living with dementia, and an old age support ratio of four and a half working adults to one older adults above 65, there is a growing number of residential aged care facilities developed to accommodate those who cannot, or choose not to, live in the community (Government of Singapore, 2019; Ministry of Health Singapore, 2019).…”
Section: Significancementioning
confidence: 99%
“…On the other hand studies have shown that the built environment can promote positive behaviours in people living with dementia and compensate for declining cognitive abilities. (Chaudhury, Cooke, Cowie, & Razaghi, 2017;Fleming & Purandare, 2010;Marquardt, Bueter, & Motzek, 2014) There are no validated assessments tools available in the South-East Asian region to provide an evidence-based evaluation of dementia-specific aged care facilities to inform the remodelling of existing facilities and the planning of new facilities (Sun & Fleming, 2018). The availability of a validated environmental assessment tool would provide a reliable platform of communication and evaluation for all stakeholders in Singapore working to develop best practice, evidence-based dementia enabling environments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some homes, finishes of different colours may be allowed to distinguish the different function zones (see Figure 2(a)). 37 A high colour contrast of the finishes can highlight important elements, while low colour contrast may reduce unwanted visual stimulation and may help older persons with dementia to identify the key information or features of a space. 38…”
Section: Literature Reviewmentioning
confidence: 99%